2000
DOI: 10.1046/j.1365-2273.2000.00391.x
|View full text |Cite
|
Sign up to set email alerts
|

Changes in snoring during natural sleep identified by acoustic crest factor analysis at different times of night

Abstract: Sleep nasendoscopy can be used to identify the site of snoring but questions remain about how well a short assessment during drug-induced sleep reflects the natural condition. To investigate the uniformity of snoring during natural sleep we studied five patients (three men, two women) referred by their GPs for treatment of their snoring. A digital audio tape recorder captured the free-field snore sound at different times of night in hospital. Acoustic Crest Factor values were calculated on the 15 recordings ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
21
0
1

Year Published

2005
2005
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 9 publications
0
21
0
1
Order By: Relevance
“…Although DISE has been shown to be reliable, some critics of the technique suggest that sedative-induced sleep only provides a small window into the complex and variable patterns of natural sleep. [25][26][27] The present study demonstrates a more dynamic approach to DISE. The surgeon actively manipulated the upper airway with a NPT to better understand the interplay of the different sites of obstruction.…”
Section: Discussionmentioning
confidence: 61%
“…Although DISE has been shown to be reliable, some critics of the technique suggest that sedative-induced sleep only provides a small window into the complex and variable patterns of natural sleep. [25][26][27] The present study demonstrates a more dynamic approach to DISE. The surgeon actively manipulated the upper airway with a NPT to better understand the interplay of the different sites of obstruction.…”
Section: Discussionmentioning
confidence: 61%
“…The probability of obstructive sleep apnea syndrome (OSAS) is 3.2 times higher in snorers than in nonsnorers,4 and a snoring analysis system could help to provide further indication of level of risk. Several studies have shown differences in acoustic snoring characteristics between patients with OSAS and simple snorers 5–8. Usually a few manually isolated snores are analyzed, with an emphasis on postapneic snores in OSAS patients.…”
Section: Introductionmentioning
confidence: 99%
“…However, endoscopies under a propofol‐induced sleep have become highly preferable due to the absence of deleterious side effects of midazolam such as vomiting, headache, and respiratory depression . Although there are supporters of drug‐induced nasal endoscopy, there are many discussions regarding the notion that a drug‐induced state does not reflect the patient's normal sleep and that this procedure might lead to errors in the determination of the obstruction localization due to excessive muscle relaxation …”
Section: Discussionmentioning
confidence: 99%